2022
DOI: 10.1111/jch.14619
|View full text |Cite
|
Sign up to set email alerts
|

Association of occupational noise exposure with hypertension: A cross‐sectional study

Abstract: The effects of chronic occupational noise exposure on hypertension are debated. We aimed to investigate the association between occupational noise exposure and the prevalence of hypertension. The cross‐sectional data were collected from 2017 to 2018 using occupational physical examination data from a local aircraft manufacturing enterprise in Xi'an. We categorized occupational noise exposure as high (≥85 dBA) and low noise exposure (< 85 dBA). Logistic regression analysis was performed to evaluate the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
1
1
0
1
Order By: Relevance
“…Results showed that exposure to high noise (>85 dB(A)) caused a 30% higher risk for hypertension compared to lower exposure, while in young adults, the odds were 70%. In accordance with this study, recent evidence from China shows that workers in Wuhan exposed to occupational noise >85 dB(A) had a higher rate of hypertension (21%), suggesting that more rigorous measures should be taken in the industries to ensure cardiovascular protection [37]. The dose-response relationship between noise and hypertension was confirmed also in automobile manufacturing workers [38].…”
Section: Hypertension Noise and Air Pollutionsupporting
confidence: 87%
“…Results showed that exposure to high noise (>85 dB(A)) caused a 30% higher risk for hypertension compared to lower exposure, while in young adults, the odds were 70%. In accordance with this study, recent evidence from China shows that workers in Wuhan exposed to occupational noise >85 dB(A) had a higher rate of hypertension (21%), suggesting that more rigorous measures should be taken in the industries to ensure cardiovascular protection [37]. The dose-response relationship between noise and hypertension was confirmed also in automobile manufacturing workers [38].…”
Section: Hypertension Noise and Air Pollutionsupporting
confidence: 87%
“…Higher rate of hypertension was found among workers exposed to occupational noise in Wuhan (21.0%) (Wang et al, 2022). The study by Wang et al (2023), of the 4746 respondents (median age 43 years and 73.4% male), 9.57% (454/4746) had hypertension and 32.4% (1540/4746) had high noise exposure.…”
Section: Introductionmentioning
confidence: 84%
“…В 1984 г. S. Belli et al, изучив состояние здоровья работников текстильной промышленности, показали увеличение распространённости стабильной артериальной гипертензии среди обследованных лиц [8]. Впоследствии данное утверждение неоднократно подтверждалось другими исследователями [9][10][11]. В научных работах последних лет обобщены данные по влиянию шума на сердечно-сосудистую систему.…”
Section: Introductionunclassified